Revisiting Barter under the CISG - Horowitz, Andrew J (Journal of Law and Commerce, 2010)
As the United Nations Commission on International Trade Law (hereinafter “UNCITRAL”) circulated a draft of what eventually became the United Nations Convention on Contracts for the International Sales of Goods (hereinafter “CISG”), it examined the need for uniform law with respect to barter transactions. At that time in 1978, various international organizations were concerned that, while barter transactions were infrequent at the domestic level, such transactions carried growing importance in international trade.